RENEWABLE ENERGY: A HISTORICAL AND THEORETICAL OVERVIEW (Third Sector Social Economic Review, 2020)
Technological developments have affected the economy throughout history. If this development takes place in a very important sector such as energy, its impact on the economy is expected to be stronger. Because the economy depends on production and energy is the basic input of production. The increase in the use of renewable energy on a global scale in the last two decades can be considered as a sign of a significant change. This situation is also reflected in the economic literature. It is observed that an important literature has developed in this regard. The aim of this study is to introduce the literature on renewable energy. It is also to analyze studies on renewable energy. The findings of the studies in the literature were examined. According to the studies in the economic literature, renewable energy use has strong effects on important macroeconomic variables such as economic growth, unemployment and foreign trade. In addition, the environment is another factor affected by renewable energy use. When the studies are analyzed, it is understood that this situation has great similarities for developed and developing countries
Keywords: Renewable energy; Economic growth; Carbon dioxide emission; Unemployment